STUDI FENOMENOLOGI:PENGALAMAN PRIMIPARA POST SECTIO CAESARIA (SC) YANG MENYUSUI DENGAN BANTUAN BANTAL ABIMANYU (AGAR BUNDA BISA MUDAH MENYUSUI ) (Phenomenology Study: Experience Of Primiparaous Post Sectio Caesaria (SC) Who Breastfeeds With Abimanyu Pillo - Wahyuni, Sylvia Dwi; Muhtadi, Fatichul; Pradanie, Retnayu (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2018)
Introduction. Mother with primiparaous experience got problems while breastfeeding between the lack of mother's knowledge of proper breastfeeding. There are some obstacles mother didn’t give breast milk to the baby of which was mother of birth with method of Sectio Caesaria. Conditions of pain relieved pain relative inhibit breastfeeding process. One way to improve comfort and reduce pain was used of aids in the form of abimanyu pillows. This studied aims to understand more deeply about the experience of primipara post SC who suckle with the help of abimanyu pillow. Method. This research was qualitative research with descriptive phenomenology design, data obtained through indepth interview. Participants amounted to eight people including primipara post Sectio Caesaria who breastfeeded used abimanyu pillow. Sampling technique used in this research was purposive. Data analysis in this research using Colaizzi method. Result. This research identifies nine themes: 1) Primipara constraint post-feed breastfeeding;2) Primipara support during breastfeeding; 3) Perception of breastfeeding; 4) Myths during breastfeeding; 5) Hope; 6) Positive perception; 7) Negative perceptions; and 9) edesign.Conclusion:The advantages of abimanyu pillows, namely: comfort, suitability of shape and design and ease of attachment of the baby.